
3个回答
展开全部
解:1+2得-2y=4
y=-2
把y=-2代入1得5x=-4-z
x= -4-z/5(是分数)标上4
把4,y=-2代入2得-4-z-4-4z=3
-8-5z=3
5z=-11
z=-11/5
把z=-11/5,y=-2代入2得5x-4+44/5=3
5x=-9/5
x=-9/25
所以x=-9/25
y=-2
z=-11/5
y=-2
把y=-2代入1得5x=-4-z
x= -4-z/5(是分数)标上4
把4,y=-2代入2得-4-z-4-4z=3
-8-5z=3
5z=-11
z=-11/5
把z=-11/5,y=-2代入2得5x-4+44/5=3
5x=-9/5
x=-9/25
所以x=-9/25
y=-2
z=-11/5
展开全部
5x-3y+z=2-------(1)
5x+2y-4z=3------(2)
-5x+y-z=2------(3)
(1)+(3), -2y=4, y=-2.
(2)+(3), 3y-5z=5, -6-5z=5, z=-11/5
把y=-2, z=-11/5代入(1), 5x+6-11/5=2, x=-9/25.
x=-9/25, y=-2, z=-11/5.
5x+2y-4z=3------(2)
-5x+y-z=2------(3)
(1)+(3), -2y=4, y=-2.
(2)+(3), 3y-5z=5, -6-5z=5, z=-11/5
把y=-2, z=-11/5代入(1), 5x+6-11/5=2, x=-9/25.
x=-9/25, y=-2, z=-11/5.
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
5x-3y+z=2 (1)
5x+2y-4z=3 (2)
-5x+y-z=2 (3)
(1)+(3)
-2y=4
y=-2
(2)+(3)
3y-5z=5
z=-11/5
代入(1)
5x+6-11/5=2
x=-9/25
x=-9/25
y=-2
z=-11/5
5x+2y-4z=3 (2)
-5x+y-z=2 (3)
(1)+(3)
-2y=4
y=-2
(2)+(3)
3y-5z=5
z=-11/5
代入(1)
5x+6-11/5=2
x=-9/25
x=-9/25
y=-2
z=-11/5
追问
真错了
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询